Survival and genomic stability of Yersinia enterocolitica in environmental Acanthamoeba spp - Chiani, Paola; Michelacci, Valeria; Delibato, Elisabetta; Ventola, Eleonora; Mannan, Samra; Marra, Manuela; Libri, Valentina; Rodríguez-Expósito, Rubén L.; Reyes-Batlle, Maria; de Fuentes, Isabel; Lorenzo-Morales, Jacob; Morabito, Stefano; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionFree-living amoebae (FLA) are widespread protozoa that can host bacterial pathogens, promoting their persistence in the environment. Yersinia enterocolitica, a foodborne zoonotic pathogen, has been detected within amoebae, but its intracellular dynamics remain unclear.MethodsIn this study, we explored the interaction between three Y. enterocolitica strains—differing in biotype and virulence gene profile—and two Acanthamoeba spp.—a reference strain and a wild environmental isolate.Results and discussionAll strains were internalized and survived up to 8 days in the collection strain and 16 days in the wild isolate. Intracellular persistence did not affect amoebal integrity or bacterial virulence profiles. Whole genome sequencing (WGS) revealed high genomic stability across strains, though specific mutations—such as in the igaA gene, involved in stress response—emerged after persistence in the collection strain. These findings suggest that Acanthamoeba spp. not only shields Y. enterocolitica from environmental stress but may also influence its genome and adaptive potential. This work expands the current understanding of Y. enterocolitica biology and highlights the role of FLA as reservoirs and potential drivers of bacterial evolution. Their contribution to the bacteria persistence and gene exchange warrants further investigation, particularly in the context of antimicrobial resistance and food safety.